curricular innovation in the university - Callejas Restrepo, María Mercedes; Gómez Gómez, Leonor; Gutiérrez, Martha Cecilia; Pardo Novoa, Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2013)
The 21st century sets out new challenges to universities and university professors,who have to debate on the quality of education, the requirements on the teaching and learning, and the proposed curricula for the professional and disciplinary training in the university. In this context, research groups from four Colombian universities have developed a project in order to articulate therelationshipswithin the training of university professors, through the research of their practices and processes of curricular innovation. With such a goal the conformation of pedagogical collectives is promoted, and a reflective process about their pedagogical styles is generated (Callejas&amp,Corredor, 2002). Action research as a methodology and strategy of professional evelopment is proposed (McKernan, 1999), observation-reflection, planning-action, and then back to observation-reflection.Video recordings of classes, individual and group observation of the recordings, and individual and group interviews that favor reflection processes about the dimensions of the pedagogical style are performed. The analysis of the practice is guided by a complex, investigative and comprehensive vision of the curriculum that articulates theory and practice. The critical recognition that teachers do about their own pedagogical style favors the evolution of their ideas and guides them to start a process of curricular innovation.